Molecular and immunological analysis of hen's egg yolk allergens with a focus on YGP42 (Gal d 6). (March 2016) - De Silva, Chamika; Dhanapala, Pathum; Doran, Tim; Tang, Mimi L.K.; Suphioglu, Cenk
Highlights: Sera of 25 egg white allergy patients demonstrated IgE binding for egg yolk proteins. Mass spec analysis revealed Gal d 6 as the important allergen of egg yolk. Recombinant Gal d 6 (rGal d 6) inhibited IgE binding to crude egg yolk by up to 30%. This is the first report of concomitant sensitization to egg white and yolk proteins. rGal d 6 has the potential to be used in diagnosis and immunotherapy of egg allergy. Abstract: Allergy to hen's (Gallus domesticus) egg white is one of the most common forms of food allergy. Allergy to hen's yolk also exists however, to a lesser extent when compared to egg white allergy. Two minor allergens from the hen's egg yolk known as α-livetin (Gal d 5) and YGP42 (Gal d 6) were discovered recently. In this study, we investigated whether sensitization to egg white is associated with reactivity to egg yolk as well. Sera obtained from 25 patients with allergy to egg white were tested for specific IgE binding for egg yolk proteins through western immunoblotting. 36% of patients were found with true IgE-sensitization against egg yolk proteins. It was found that most of the IgE reactive yolk proteins were fragments of major precursor proteins of hen; vitellogenin-1 (VTG-1), vitellogenin-2 (VTG-2) and apolipoprotein B (Apo B). The egg yolk allergen Gal d 6 is the C-terminal part of VTG-1 and was found to be allergenic in significant percentage of egg white allergy patients. These results highlight the significance of Gal d 6 as an important allergen of egg yolk. Therefore, the secondary aim of this study involved developing a recombinant version of YGP42 in an Escherichia coli expression system. Recombinant Gal d 6 (rGal d6) was expressed as a fusion peptide with a 6 × His tag and purified using metal chelating resin. The inhibition ELISA results showed that rYGP42 was IgE reactive and was able to inhibit IgE binding to crude egg yolk (CEY) by up to 30%. Traditionally, it was thought that allergy to egg yolk occurred independently from sensitization to egg white. This study underlies the importance of concomitant sensitization to egg yolk proteins in patients allergic to egg white. Evidence reported in this study strongly suggests that egg yolk has potentially undiscovered allergens and therefore warrants further investigation. Furthermore, IgE reactive Gal d 6 presented in this study has the potential to be used in diagnosis and immunotherapy to treat egg allergy.